Minerva Plaza – A New Technology-rich Learning Environment. (16th January 2015) - Ruismäki, Heikki; Salomaa, Riikka-Liisa; Ruokonen, Inkeri
Abstract: This article focuses on a new learning environment called Minerva Plaza that was opened in 2012 at the Faculty of Behavioural Sciences at the University of Helsinki. The purpose of the study is to find out how the new space has been used and received by the students, teachers and visitors, and to form a good overall picture of the strengths and weaknesses of the space as a technology-rich learning environment. Plans for the use of the space at Minerva Plaza are also discussed. The research is a case study where the Informant is a person who has worked as an educational technology coordinator at Minerva Plaza since it opened. One of the main goals is to make the most of the broad practical experience, insight, and theoretical knowledge that the Informant has about the use of the space.